1997
DOI: 10.1016/s0885-3924(97)00019-5
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell-related pain: Perceptions of medical practitioners

Abstract: Pain is the most common problem encountered by patients with sickle cell disease (SCD). We report the results of a survey sent to hematologists and emergency department (ED) physicians regarding their perceptions and practices concerning pain and its management. Hematologists and ED physicians differed considerably in their perceptions about the natural history of the pain, and about the percentage of patients who are addicted to analgesics. Fifty-three percent of the ED physicians and 23% of the hematologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
127
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(130 citation statements)
references
References 9 publications
2
127
1
Order By: Relevance
“…[10][11][12][13] It is a common perception of emergency physicians and staff that SCD patients presenting to the ED are opioid dependent, and this belief may lead to inconsistent or inadequate treatment. 14,15 Both physicians and nurses tend to overestimate the prevalence of addiction in the SCD population, which has been documented to range from 0% to 11%. 12,15 Further exploration is required to fully understand the frequent use of the ED, which may represent a higher acuity of illness, lack of access to a sickle cell provider, or other complex psychosocial issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] It is a common perception of emergency physicians and staff that SCD patients presenting to the ED are opioid dependent, and this belief may lead to inconsistent or inadequate treatment. 14,15 Both physicians and nurses tend to overestimate the prevalence of addiction in the SCD population, which has been documented to range from 0% to 11%. 12,15 Further exploration is required to fully understand the frequent use of the ED, which may represent a higher acuity of illness, lack of access to a sickle cell provider, or other complex psychosocial issues.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Both physicians and nurses tend to overestimate the prevalence of addiction in the SCD population, which has been documented to range from 0% to 11%. 12,15 Further exploration is required to fully understand the frequent use of the ED, which may represent a higher acuity of illness, lack of access to a sickle cell provider, or other complex psychosocial issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, adequate pain control has been problematic for several reasons, including tolerance, dependence, sedation, respiratory depression, nausea, constipation, and pruritus. Furthermore, because of the fear among many health professionals that patients will become addicted, many sickle cell patients in pain management are under-treated with opioids (1,7,8).…”
mentioning
confidence: 99%
“…Previous work has shown that adults with SCD are met with high levels of mistrust, with health professionals believing that they exaggerate their pain and exhibit significant drug seeking behavior [13,14]. Based on parental desire to have more input into the care of their child, it is reasonable to assume that the lack of objective findings in children with SCD makes it more difficult for hospital staff to fully interpret the disease severity.…”
Section: Discussionmentioning
confidence: 99%